Respuesta :

Answer:

I'm pretty sure its 1

Step-by-step explanation:

because if y = 1. 1 by the power of 3 is 1, and y by the power 2 is 1. 1- 10 is -9 . -9 times 1 equals -9, and -9 equals -9 therefore it's a true statement

Step-by-step explanation:

y³ (y² − 10) = -9y

Move everything to one side:

y³ (y² − 10) + 9y = 0

Factor out common term:

y (y² (y² − 10) + 9) = 0

Distribute:

y (y⁴ − 10 y² + 9) = 0

Factor:

y (y² − 1) (y² − 9) = 0

Solve:

y = 0, ±1, ±3

Since y > 0, the two possible values for y are 1 and 3.